An Effective Self-directed Personalized Learning Environment for Engineering Students During the COVID-19 Pandemic - Balakrishnan B.; Long C.Y. (American Society for Engineering Education, 2023)
Computer aided instruction; Motivation; Teaching; Engineering undergraduates; Intrinsic motivation; New dimensions; Personalized learning environments; Self-directed; Teaching and learning; Engineering education